A Multidisciplinary Approach to Rhinoplasty: The Facial Plastic Surgeon and the Psychologist - Auer, Deborah; Saroha, Sarup; Unadkat, Samit N.; Saleh, Hesham A. (Facial Plastic Surgery, 2025)
Rhinoplasty is one of the most frequently requested aesthetic procedures. However, a subset of patients presents with complex psychological profiles that can adversely impact surgical outcomes. Early psychological assessment is crucial to optimizing patient safety and satisfaction.This narrative review aims to explore the role of integrated psychological assessment within multidisciplinary facial plastic surgery services. It hypothesizes that early psychological input improves patient selection, manages expectations, and reduces revision rates.Narrative review.We conducted a structured narrative review of PubMed/MEDLINE, PsycINFO, Embase, and Scopus (from inception to June 2025), supplemented by clinical experience from a high-volume United Kingdom rhinoplasty center. Search terms included rhinoplasty, psychology, BDD, screening, and multidisciplinary care. Eligible sources comprised peer-reviewed studies, reviews, and guidelines on psychological assessment or outcomes in aesthetic rhinoplasty.Integrated psychological assessment can identify patients at risk of dissatisfaction, enhance patient selection, reduce revision surgeries, and improve overall outcomes.Multidisciplinary collaboration between surgeons and psychologists improves rhinoplasty outcomes, enhances patient safety, and supports the ethical principle of nonmaleficence.
Keywords: rhinoplasty; plastic surgery; psychology; body dysmorphic disorders; multidisciplinary team